Antioxidative activity and health benefits of anthocyanin-rich fruit juice in healthy volunteers. (12th August 2019) - Bakuradze, Tamara; Tausend, Angelina; Galan, Jens; Groh, Isabel Anna Maria; Berry, David; Tur, Josep A.; Marko, Doris; Richling, Elke
Abstract: Oxidative cell damage has been linked to the pathogenesis of numerous diseases such as atherosclerosis, type 2 diabetes, and cancer. The consumption of foods rich in polyphenols (e.g. anthocyanins) has been shown to exert preventive effects against such diseases. We investigated the biological effects of anthocyanin-rich fruit juice in a 9-week, placebo-controlled intervention study with 57 healthy male volunteers. The study design encompassed an initial 1 week of wash-out, followed by 8 weeks of intervention period with anthocyanin-rich fruit juice or placebo. The anthocyanin-rich fruit juice demonstrated DNA-protective and antioxidant effects; however, the placebo beverage, rich in vitamin C, showed similar effects based on the tested biomarkers. A significant reduction in background and total DNA strand breaks was observed in both groups within 24 h as well as after 8 weeks of intervention. Only anthocyanin-rich fruit juice consumption provided a significant reduction in body fat and an increase in fat-free mass. The activity of superoxide dismutase (SOD) was significantly elevated after consumption of anthocyanin-rich fruit juice. Both groups showed decreased levels of LDL and total cholesterol (TC) within the first week of the intervention. Similar results in both groups could be explained by the relatively high vitamin C contents of both beverages (>500 mg/L), which may have masked the effects of anthocyanins and other antioxidants in the studied juice. Taken together, anthocyanin-rich fruit juice as well as the placebo drink, both of which had high vitamin C content, can improve DNA integrity and might influence lipid metabolism in humans.